Influence of light on callus generation and in vitro plant culture - Ruíz-Rivas, Magali; Martínez-Núñez, Marcelino; Vera-Hernández, Pedro Fernando; Martínez-Romero, Esperanza; Rosas-Cárdenas, Flor de Fátima (Revista Mexicana de Ciencias Agrícolas, 2022)
In vitro culture systems are important in the field of plant biotechnology. It has been observed that some factors, including light, affect tissue development under in vitro culture conditions. The objective of this work is to know the effect of light intensity on the development of tissues from seeds under in vitro culture conditions for the generation of seedlings and calluses, in order to favor the times and the regeneration of species of agronomic interest for their comprehensive use. In this work, different light intensities were tested, it was possible to obtain seedlings with calluses, demonstrating that the intensity of light influences the type and development of dedifferentiated structures and that this effect varies inter and intraspecies. By regenerating plant tissues from seedlings, it was found that apical meristem shoots are the most efficient type of explant for clonal regeneration of tobacco and tomato plants. This study is the first to present the effect of light intensity on seeds for the production of seedlings and calluses in different plant species, including a combination of different tissues and explants that could be used to obtain different plant structures for biotechnological purposes.